Region Refinement Technique In MGEAR Protocol To Enhancing Sensor Node Life Time - Jamwal, Preeti; Mahajan, Sonam (International Journal of Computer Sciences and Engineering, 2025)
There are number of energy efficient techniques used to enhance the network life time one of them is gateway based energy-efficient routing protocol (M-GEAR) this protocol is based on the node which is rechargeable and divides network into four logical regions on the basis of the location from the Sink. In this paper we use the Enhanced gateway based energy-efficient technique which works on the basis of multilevel multihop technique with CHs and gateway nodes in region 2 and region 3 and the selection of the cluster heads in these region is based on the energy concept, which improves the network life time by minimizing the data loss and cluster failure